Pemanfaatan Zakat dan Wakaf Sebagai Instrumen Efektif dalam Meningkatan Kesejahteraan Masyarakat - Ali Murtadho; Muhammad Defri; Indra Ezha Noor Rizhal; Hafid Gunawan; Muhammad Wildan (TADHKIRAH: Jurnal Terapan Hukum Islam dan Kajian Filsafat Syariah, 2025)
This article discusses the dynamics of zakat fatwas in Indonesia, focusing on the process of fatwa formation by the Indonesian Ulema Council (MUI) and the National Zakat Agency (BAZNAS). This study highlights how zakat fatwas are not only religious in nature, but also closely related to social and political dimensions. Through a normative and sociological approach, this article examines how zakat fatwas respond to social changes, including the expansion of zakat objects and the integration of zakat management into the national system. This study shows that zakat fatwas play an important role in strengthening zakat governance and forming collective awareness of the community in carrying out zakat obligations systematically and in an organized manner.